INVENTARISASI POTENSI LOGAM TANAH JARANG MENGGUNAKAN METODE GEOFISIKA DI DAERAH AIRBARA, KABUPATEN BANGKA SELATAN, KEPULAUAN BANGKA BELITUNG - Silti Salinita; Asep Bahtiar Purnama; Andi Agus Nur; Yuyun Yuniardi (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2023)
The development of Rare Earth Elements (REE) based industries is still facing obstacles, even though rare earth elements have a very strategic role in the future. The purpose of this study is to determine the potential of sulfide-bearing rock resources from the modeling results as a basis for deciding LTJ prospect areas that can be further developed for the preparation of Mining Business Permit Areas. The research area is in Airbara Village, Airgegas District, South Bangka Regency, Bangka Belitung Islands Province. The method used is geoelectrical Induced Polarization (IP) measurements to determine the subsurface geological conditions. Based on direct field observations, the geomorphology of the study area is divided into three geomorphological units: lowland fluvial units, denudational plain units, and low intrusion hill units. The rock units in the study area are divided into three rock units from young to old: alluvium units, granite rock units, and alternating sandstone and clay units. Geoelectrical measurements of induced polarization were carried out on eight tracks located in 2 blocks of the study area, namely five tracks in the ABA block and three in the ABB block. Based on the distribution of resistivity values, the ABA05 line has the highest value, namely 33.1 Ωm to 2,398,833 Ωm. Tracks ABA01, ABA05, ABB07, and ABB08 have relatively moderate to high chargeability values. The potential for sulfide-bearing rock resources in the ABA block is estimated at 261,818 m3. If the rock density value is assumed to be 2.65 gr/cm3 or 2.65 tons/m3, then the total rock resource carrying sulfide minerals in this area is 693,818 tons. The potential for sulfide-bearing rock resources in the ABB block is estimated at 1,590,708 m3. If the rock density value is assumed to be 2.65 gr/cm3 or 2.65 tons/m3, then the total rock resource carrying sulfide minerals in this area is 4,215,376 tons. The actual rock resources taking sulfide minerals from the results of the 3D modeling of the IP and resistivity methods amount to 4,909,194 tons from an area of ​​1,296.2 Ha.